Analisa Desain Troli Lipat (Studi Kasus Tada Toko dan Mall) - Iqbal Hadliri; Prantasi Harmi Tjahjanti; Wijaya Kelana Nur Soleh (Jurnal Abdimas ADPI Sains dan Teknologi, 2023)
The trolley equipment that is typically used in malls or stores cannot be folded or bent to take up enough space for you to move it anyplace. Because using Solidworks software, the goal of this research is to develop a collapsible trolley. The Von Misses stress test was used to test folding and general purpose trolley frames for loads of 35 kgf, 245 kgf, and 875 kgf. According to the findings at a weight of 35 kgf, typical goods carts have a greater Von Misses stress of 796.6e+008N/m2. A regular goods trolley's high Von Misses stress is 7966e+009N/m2 at a weight of 245 kgf. On conventional goods trolleys, the Von Misses stress reaches 962.4e+009N/m2 at the maximal load, which is 875 kgf. Because folding trolleys use hollow iron, which is lighter, it follows that standard goods trolleys have a higher strength than folding trolleys, albeit folding trolleys are considerably more effective.